Induced Expression of Xerophyta viscosa XvSap1 Gene Enhances Drought Tolerance in Transgenic Sweet Potato - Mbinda, Wilton; Dixelius, Christina; Oduor, Richard (Frontiers in Plant Science, 2019)
Drought stress often leads to reduced yields and is perilous delimiter for expanded cultivation and increased productivity of sweetpotato. Cell wall stabilization proteins have been identified to play a pivotal role in mechanical stabilization during desiccation stress mitigation in plants. They are involved in numerous cellular processes that modify cell wall properties to tolerate the mechanical stress during dehydration. This provides a plausible approach to engineer crops for enhanced stable yields under adverse climatic conditions. In this study, we genetically engineered sweetpotato cv. Jewel with XvSap1 gene encoding a protein related to cell wall stabilization, isolated from the resurrection plant Xerophyta viscosa, under stress-inducible XvPSap1 promoter via Agrobacterium-mediated transformation. Detection of the transgene by PCR, Southern blot and qRT-PCR analyses revealed the integration of XvSap1 in the three independent events. Phenotypic evaluation of shoot length, number of leaves and yield revealed that the transgenic plants grew better than the wild type plants under drought stress. Assessment of biochemical indices during drought stress showed higher levels of chlorophyll, free proline and relative water content, decreased lipid peroxidation in transgenic plants than wild types. Our findings demonstrate that XvSap1 enhances drought tolerance in transgenic sweetpotato without causing deleterious phenotypic and yield changes. The transgenic drought tolerant sweetpotato lines provides a valuable resource as drought tolerant crop on arid lands of the world.